An Empirical Analysis of the Ethical Reasoning of Tax Practitioners - Doyle, Elaine; Frecknall-Hughes, Jane; Summers, Barbara 1944- (2013)
How tax practitioners approach ethical dilemmas remains generally unexplored in academic literature. We use here Rest’s original Defining Issues Test (Development in judging moral issues. Minneapolis: University of Minnesota Press, 1979; Moral development. Advances in research and theory. New York: Praeger Publishers, 1986), combined with a tax context-specific test and in conjunction with a control group of non-tax specialists, to examine tax practitioners’ moral reasoning in a social and tax context. We investigate: (i) the effect of a tax context on issues raised (finding that practitioners generally reason at lower levels than in social scenarios); (ii) whether the profession attracts people who reason at certain levels (finding that it does not); and (iii) whether practitioners are affected by training/socialization in their professional context (finding that that they are).
Keywords: Tax practitioner; Tax practice; Revenue practitioner; Moral Reasoning; DIT